Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae) - Tavares, Marcos; Santana, William (Zootaxa, 2018)
The genus Scyramathia A. Milne-Edwards, 1880 (type species Amathia carpenteri Norman in Wyville Thomson, 1873) is herein removed from the synonymy of Rochinia A. Milne-Edwards, 1875 (type species R. gracilipes A. Milne-Edwards, 1875) and a new genus, Minyorhyncha, is established for Amathia crassa A. Milne-Edwards, 1879, a species previously placed in the genus Rochinia. The genus Anamathia Smith, 1885 (type species Amathia rissoana Roux, 1828), widely regarded as a synonym of Rochinia, is confirmed as a valid genus. The morphological differences between Rochinia (as revealed by its type species), Anamathia, Scyramathia and Minyorhyncha are discussed and illustrated. The strong ontogenetic changes in Minyorhyncha crassa n. gen., n. comb. are also discussed and illustrated. Lectotypes are selected for Rochinia gracilipes A. Milne-Edwards, 1875, and Amathia agassizii Smith, 1882, a junior synonym of Minyorhyncha crassa n. gen., n. comb.